Measurement of Muon Neutrino CC Interactions With Two-Proton Final State in MINERvA - Syrotenko, Vladyslav (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2026.; Submitted to the Dept. of Physics.; Advisor: Hugh Gallagher.; Committee: W. Anthony Mann, Kevin McFarland, Mark Hertzberg, and Peter Love.; Keyword: Physics